Biocatalytic α‐Oxidation of Cyclic Amines and N‐Methylanilines for the Synthesis of Lactams and Formamides. Issue 6 (15th February 2017) - Zheng, Daijun; Zhou, Xiaojian; Cui, Baodong; Han, Wenyong; Wan, Nanwei; Chen, Yongzheng
Abstract: An environmentally friendly method for the synthesis of lactams and formamides through the biocatalytic α‐oxidation of amines was developed by employing Pseudomonas plecoglossicida ZMU‐T04 as a biocatalyst. In this biocatalytic process, the α‐oxidation of cyclic amines and N ‐methylanilines proceeded smoothly to give the corresponding amides in low to high yields. Furthermore, it was demonstrated that synthetic 3, 4‐dihydroquinolin‐2(1 H )‐one could be used as a key precursor of antidepressant bioactive molecules. The mechanism of this biocatalytic α‐oxidation process was investigated by isotope‐ labeling experiments. Abstract : The big [O] : A highly regioselective, environmentally friendly method for the synthesis of amides from amines is developed. With biocatalytic α‐oxidation, various cyclic amines and N ‐methylanilines are oxidized smoothly to give the corresponding amides. Mechanistic studies suggest that the amide oxygen atom of this biocatalytic α‐oxidation process is derived from water.